History of Aryan Invasions to Aryan Migrations: Language and Cultural Shifts in Ancient India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
When the link between the various languages of the Indo-Europeanfamily was first discovered, it was automatically assumed that languages arespread primarily by groups of intruding invaders. Since the homeland of the IElanguages was already placed outside India, it was proposed that a group of IAspeaking invaders (who were derived from PIE speakers) had invaded Indiasometime in the middle of the 2nd millennium B.C., imposing their language onthe ‘Dravidian’ and on the other non-Aryan aboriginal inhabitants of India, byforce.